Solving teenage and young mothers’ childhood immunization hesitance and non-compliance through mobile immunization friendly service for working mothers in Ibadan, Nigeria (2023)
Mobile Immunization for working mothers (SheVaccs) is an intervention targeted at working mothers in the informal markets of Ibadan to address problem of vaccine hesitance and drop-out among different categories of mother. These mothers have great responsibilities – keeping their homes stable and their children healthy. But these mothers have challenges of different magnitudes that prevented them from immunizing their children, and for teenage mothers they are faced with socio-cultural and socio-economic obstacles and have not responded positively to childhood immunization. In relation to these challenges, SheVaccs intervention study provided friendly immunization, counselling services, and information around vaccination schedules to working mothers in Ibadan, Nigeria. The intervention covered adolescent and young mothers’ population in the selected markets. Mobile clinic was set up in 3 different purposively selected markets in Ibadan. Data for this were collected through qualitative methods of observation and 21 in-depth interviews with teenage mothers, and 6 key informant interviews with their significant others. All data were subjected to content analysis. The age range of others involved in the study was between 17-23 years, almost all participants had no post- secondary school education. All mothers in this study find it difficult to attend conventional immunization centers, due to stigmatization, subtle hostility and embarrassment they experienced during pregnancy and after in some of these centers. Many of them were ignorant and have also been mis-socialized into motherhood and childcare. They preferred an immunization service that is mobile, with “strangers” who are friendly, understanding and will not judge them for ‘’being anti-social’’. They preferred Mobile clinic because it does not waste time (5 to 7 minutes), which allows them to do other thing or concentrate on their job (source of survival), provide quick, friendly counselling and intervention for their immunization related worries. Friendly Mobile immunization services targeted at teenage and young mothers will remove clog of stigmatization and hostility and minimize incidence of childhood Immunization Hesitance and non-compliance to schedule.